Analisis Perilaku Usaha Peternak Kerbau di Pulau Moa Kabupaten Maluku Barat Daya - Miiriam Novarina Terlewan; Semuel S.J. Tomatala; Piter M Ririmasse (JURNAL PERTANIAN KEPULAUAN, 2021)
This study aims to analyze the behavior of farmers in buffalo farming in Moa District, Southwest Maluku Regency. The survey was conducted in three sample villages, namely Tounwawan Village. Klis Village and Werwaru Village. The variable observed were the breeders age, education level occupation,family dependents,buffalo ownership and number of buffalo. The main variables are knowledge, Attitudes and actions towards buffalo farming. The results showed that the behavior of breeders based on the level of knowledge of farmers in the buffalo farming was in the agree (S) category, the proportion of which was 75.8%, meaning that the breeders had good knowledge in the buffalo livestock business, the attitude of the breeders was in the Strongly Agree (SS) category. with a proportion of 80.4%,it means that in running a buffalo catlle business,the breeders show a very good attitude, while the actions of the breeders are in the category of doing (M) the proportion is 53.33% meaning that the farming in his business implements variour technical measures in business management her.